Myofunctional orofacial examination tests: a literature review - Delal Dara Kilinc; Duygu Mansiz (BMC, 2023)
Abstract Introduction Myofunctional orofacial examination (MOE) is an important tool for the assessment of the stomatognathic system and orofacial functions, and the early diagnosis of orofacial myofunctional disorders. Therefore, the purpose of the study is to scan the literature and determine the most preferred test for myofunctional orofacial examination. Materials and Methods A literature review was conducted to collect information. Pubmed and ScienceDirect database was explored by using keywords gained by MeSH (Medical Subject Headings). Results Fifty-six studies were retrived from the search and all of the studies were screened and evaluated regarding the subject, aim, conclusions and the orofacial myofunctional examination test they used. It has been observed that traditional evaluation and inspection methods have been replaced by newer and methodological approaches in recent years. Conclusions Although the few tests used differ, 'Orofacial Examination Test With Scores' (OMES) was found to be the most preferred myofunctional orofacial evaluation method from ENT to cardiology.